Dampak Abu Vulkanik Erupsi Gunung Kelud dan Pupuk Kandang terhadap Ketersediaan dan Serapan Magnesium Tanaman Jagung di Tanah Alfisol - Suntoro Suntoro; Hery Widijanto; Sudadi Sudadi; Eko Eri Sambodo (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2014)
The impact of Volcanic Ash of Kelud Eruption and Manure on Availability and Magnesium Uptake of Corn in Alfisols. Impact of fresh volcanic ash on soil fertility is rarely studied mainly on nutrient availability, uptake and on plant growth. Fresh volcanic ash is primary mineral that takes time and agents such as organic materials to mineralized before it contribute to soil fertility. This study aimed to study the effect of the thickness of fresh volcanic ash of Kelud Mountain and dosage of manure on availability and uptake of Magnesium and chlorophyll content of corn in Alfisol. This is greenhouse experiment arranged in factorial completely randomized design with two treatment. The first factor is the thickness of volcanic ash: 0, 2. 4, and 6 cm, and the second factor is the dosage of manure: 0, 2 and 4 tonha-1, each treatment combination was repeated 3 times. Variables observed include exchangable-Mg , Mg uptake, and chlorophyll content of corn. The results showed that there is no interaction effect of volcanic ash and manure on exchangable-Mg, Mg uptake and chlorophyll content of corn. This proved that they affect nutrient availability in different ways. Both volcanic ash of Kelud eruptionas as well as manure increase exchangable-Mg, especially at 6 cm thickness of volcanic ash treatment, Mg-uptake and  chlorophyll content of corn leaf independently. There was a relationship between exchangable-Mg and chlorophyll content in the leaves.